Caregivers of children feel confident about using the Internet for health information. (8th April 2022) - Delemere, Emma; Maguire, Rebecca
Abstract: Background: Caregivers of children may rely on internet sources, health care providers, peers or family for health information. Objective: To examine the impact of sociodemographic factors on the use of the internet for health information by caregivers of children, and the impact on self‐efficacy, effort and frustration. Methods: Using data from the 2019 Health Information National Trends Survey, the effects of information source on self‐efficacy, effort and frustration was examined using the complex samples module of SPSS. Results: The internet was the most common source of health information for caregivers of children ( n  = 247), with high confidence, low frustration and effort reported. Younger, higher educated and higher income caregivers were significantly more likely to use the internet for health information. Information from Health Care Providers (HCPs) was associated with greater confidence, and information from peers associated with lesser effort and frustration. No significant effects on self‐efficacy, effort or frustration for online health information was noted compared to other sources. Conclusions: Efforts to reduce barriers to online health information may be required for some groups of caregivers, and health care providers may have a role to play in this.